Polymethyl Methacrylate Intraocular Lenses as Substitute for Gold Weight in Lagophthalmos Surgery: A Case Report - Koirala, Ashesh; Bista, Ankit; Joshi, Purushottam (Nepalese Journal of Ophthalmology, 2026)
Introduction: Paralytic lagophthalmos, typically resulting from facial nerve palsy, causes incomplete eyelid closure, leading to severe ocular surface desiccation, exposure keratopathy, and potential vision loss. Gold weight implantation remains the surgical standard of care for restoring gravity-assisted eyelid closure. However, the cost of gold often creates a significant barrier to treatment, particularly in developing nations or for patients without adequate insurance coverage, necessitating the exploration of affordable, readily available alternatives. Case: A 41-year-old woman developed left-sided paralytic lagophthalmos following orbital cellulitis with dacryocystitis. Observation: Persistent exposure keratopathy persisted despite the use of lubricants and previous tarsorrhaphy. Due to financial constraints, gold weight implantation was not feasible, so two polymethyl methacrylate (PMMA) intraocular lenses (IOLs) were repurposed as eyelid-loading implants and secured to the anterior tarsal surface within a submuscular pocket. Post-operative assessment showed immediate and significant improvement in eyelid closure, with maximum improvement of lagophthalmos and symptoms of exposure keratopathy. The IOL provided adequate gravitational force for effective eye closure, and the cosmetic result was satisfactory. Conclusion: Repurposing a readily available, low-cost PMMA intraocular lens offers a safe, effective, and economical alternative to gold weight implantation for managing paralytic lagophthalmos, particularly in resource-constrained settings or for patients with limited financial means. This technique should be considered a good treatment option for incomplete eyelid closure.